2015
DOI: 10.1111/1754-9485.12409
|View full text |Cite
|
Sign up to set email alerts
|

Audit of demand for after‐hours CT scanning services in RANZCR‐accredited training departments

Abstract: Introduction: The aims of this study were to measure: (i) the growth in after-hours emergency department -referred CT (ED-CT) performed in accredited training departments between 2011 and 2013; (ii) the growth in ED CT relative to growth in ED presentations at the same hospitals; and (iii) trainee workload resulting from after-hours ED CT. Methods: Ethics approval was obtained for all participating sites. Accredited training facilities in Australia and New Zealand with three or more trainees and serving one or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…CTB is an essential diagnostic tool for assessing patients with potential NTBI. However, there is a lack of a well validated CDR in place to aid in ruling out low‐risk patients for this imaging modality . In our study, only 6.6% of all included scans ( n = 10 394) reported significant clinical findings.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…CTB is an essential diagnostic tool for assessing patients with potential NTBI. However, there is a lack of a well validated CDR in place to aid in ruling out low‐risk patients for this imaging modality . In our study, only 6.6% of all included scans ( n = 10 394) reported significant clinical findings.…”
Section: Discussionmentioning
confidence: 74%
“…This suggested that an over‐referral pattern exists for CTB in Australian EDs. A 2017 study by Goergen et al found Australian and New Zealand EDs had increased their demand for after‐hours CTB between 2011 and 2013, with a 15.7% increase between 17.00 hours and 22.00 hours and a 16.8% increase between 22.01 hours and 07.30 hours of the EDs surveyed. Goergen et al commented that this has effects not only on ED length of stay and monetary expenditure but also on the workload of radiology staff, making this issue a multidisciplinary challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of normal working hours, a single radiology registrar is usually responsible for reporting all after hours CTs [1]. It can be several hours before a consultant radiologist reviews the CTs and thus it is the interpretation of the CT by the registrar that drives the initial management.…”
Section: Discussionmentioning
confidence: 99%
“…In many public hospitals a single radiology trainee is responsible for reporting all after hours CTs and a recent study of accredited training facilities in Australia and New Zealand showed a 16.2% increase in the number of 'out of hours' ED CTs performed between 2011 and 2013 [1]. Some hospitals are also opting to utilise teleradiology companies to report after-hours studies.…”
Section: Introductionmentioning
confidence: 99%
“…6 Not surprisingly, increased utilisation has resulted in increased radiology resident workload. 7 At our institution, CT scans ordered from the ED afterhours previously required a direct conversation between the radiology resident and ED staff prior to being protocolled. In our experience, this is the case in many academic institutions without a dedicated Emergency Radiology department.…”
Section: Introductionmentioning
confidence: 99%